Bottom-up and top-down processes influence contemporary patterns of mammal species richness in Australia's monsoonal tropics. (July 2020) - Stobo-Wilson, A.M.; Stokeld, D.; Einoder, L.D.; Davies, H.F.; Fisher, A.; Hill, B.M.; Mahney, T.; Murphy, B.P.; Scroggie, M.P.; Stevens, A.; Woinarski, J.C.Z.; Bawinanga Rangers,; et al.
Abstract: In recent decades severe mammal declines have occurred in the vast and uncleared tropical savannas of northern Australia. Mounting evidence suggests that feral cats ( Felis catus ), large feral herbivores and increased frequency of high-severity fires, are all contributing to declines; however, the respective influence of each threat remains unclear. There is an urgent need to quantify the relative impacts of both 'bottom-up' (i.e. the depletion of resources and habitat simplification from contemporary disturbance regimes) and 'top-down' (i.e. increased predation pressure) factors on small mammal populations to inform where, and how, remedial conservation efforts should be targeted in northern Australia. We conducted an extensive survey of mammals across ca. 370, 000 km 2 of monsoonal northern Australia using both camera-trapping and live-trapping methods. From multispecies occupancy models, we found that feral herbivore abundance, dingo abundance and feral cat occupancy were the best predictors of species richness of small (<5500 g) mammals, with species richness declining as the respective pressures increased. Our results highlight that underlying productivity has seemingly enhanced the capacity of native mammals to withstand pressures, as species that have severely declined are now more likely to occur in areas with greater productivity. We suggest that a disturbance-driven reduction in habitat complexity and productivity has significantly disrupted bottom-up processes in northern Australia, subsequently increasing top-down pressure from predation, causing severe declines across much of the native mammal assemblage. Without maintaining, enhancing or recovering habitat condition in this region, long-term conservation and recovery of mammal diversity is unlikely.